Integrated metabolomic and transcriptomic profiling elucidates the tissue-specific biosynthesis and regulation of flavonoids in Machilus nanmu - Zhang, Xiao; Xia, Changying; Zhang, Huan; Li, Wenqiao; Zhang, Zhe; Long, Nana; Yao, Renxiu; Li, Jian; Deng, Hongping (Frontiers in Plant Science, 2026)
IntroductionMachilus nanmu is a significant arborescent species of the genus Machilus (Lauraceae), exhibiting considerable potential for applications in industrial materials and healthcare. However, systematic investigations into its flavonoid metabolites and associated biosynthetic mechanisms remain limited, which significantly hinders the efficient exploitation and sustainable utilization of this species.MethodsThis multi-omics study revealed the specific accumulation pattern of flavonoids in the tissues of M. nanmu and pinpointed key structural and regulatory genes underlying their biosynthesis by integrating widely targeted metabolomics and transcriptomics data from roots, stems, and leaves.ResultsA total of 425 flavonoid compounds and 35,671 differentially expressed genes were detected. Further screening revealed 41 structural genes encoding 19 key enzymes (including PAL, CHS, FLS, UGTs, etc.), among which two UGTs (Cluster-69292 and Cluster-71935) were subcellularly localized to the cytoplasm. Furthermore, the weighted gene co-expression network analysis (WGCNA) revealed four key modules exhibiting strong correlations with flavonoid content. From these modules, four core transcription factors (TFs) from the MYB and bHLH families were identified as putative regulators of flavonoid biosynthesis.DiscussionOur findings offer the first comprehensive model of tissue-specific flavonoid accumulation in M. nanmu, enabling the dissection of its transcriptional machinery and advancing strategies for its genetic improvement and resource exploitation.